Bipolar fuzzy Lie ideals - Akram, Muhammad; Alshehri N.O. (Utilitas Mathematica, 2012)
We introduce the notion of a bipolar fuzzy Lie ideal of a Lie algebra and investigate some properties of nilpotency of bipolar fuzzy Lie ideals. We introduce the concept of bipolar fuzzy adjoint representation of Lie algebras and discuss the relationship between this representation and nilpotent bipolar fuzzy Lie ideals. We also define Killing form in the bipolar fuzzy case and study some of its properties.